COMPARING COMPANY PERFORMANCE BASED ON TYPES OF MERGERS AND ACQUISITIONS IN THE FINANCIAL SECTOR - Richard William (Sean Institute, 2023)
Some literature indicates that mergers and acquisitions generally have a negative effect on the companies involved. This study aims to analyze whether mergers and acquisitions affect the performance of financial sector companies in the short and medium term. Based on the types of mergers and acquisitions carried out, company performance is measured by profitability, enterprise value (company value), and stock returns. The sample in this study totalled 165 merger and acquisition transactions involving financial sector companies that occurred in the United States during the period from January 2009 to January 2019. Using multiple linear regression, this study found that conglomerate M&A was the best in increasing short-term performance, while horizontal M&A was the best in improving medium-term performance.